2010
DOI: 10.1590/s1808-18512010000400007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica e radiográfica da cifoplastia no tratamento das fraturas vertebrais por osteoporose

Abstract: OBJETIVO: analisar os resultados clínicos, radiológico e possíveis complicações de pacientes submetidos à cifoplastia no tratamento das fraturas por osteoporose dolorosas que não respondem ao tratamento conservador. MÉTODOS: foram avaliados 24 pacientes com fraturas osteoporóticas tratados através da cifoplastia. Destes, 19 (76%) eram do sexo feminino e 5 (24%) do masculino. A média de idade foi de 71,3 anos. A média de seguimento foi de 19 meses, variando de 3 a 29 meses. Os pacientes foram avaliados em relaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…1,2,24 Balloon kyphoplasty is a minimally invasive procedure capable of stabilizing spinal fractures and reducing pain intensity while improving function and consequently, the quality of life. 10,12,13,23,24 However, the mechanism responsible for alleviating the pain is controversial, as it can be attributed either to stabilization or to thermal injury of the nerve endings. 23,25,26 This study demonstrated short-and long-term pain relief resulting from treatment by means of kyphoplasty of the metastatic lesions of the vertebral body, agreeing with previous reports in the to better treatment outcomes, and there are doubts as to whether the correction occurs due to the positioning of the patient or during the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,24 Balloon kyphoplasty is a minimally invasive procedure capable of stabilizing spinal fractures and reducing pain intensity while improving function and consequently, the quality of life. 10,12,13,23,24 However, the mechanism responsible for alleviating the pain is controversial, as it can be attributed either to stabilization or to thermal injury of the nerve endings. 23,25,26 This study demonstrated short-and long-term pain relief resulting from treatment by means of kyphoplasty of the metastatic lesions of the vertebral body, agreeing with previous reports in the to better treatment outcomes, and there are doubts as to whether the correction occurs due to the positioning of the patient or during the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13,23,24 However, the mechanism responsible for alleviating the pain is controversial, as it can be attributed either to stabilization or to thermal injury of the nerve endings. 23,25,26 This study demonstrated short-and long-term pain relief resulting from treatment by means of kyphoplasty of the metastatic lesions of the vertebral body, agreeing with previous reports in the to better treatment outcomes, and there are doubts as to whether the correction occurs due to the positioning of the patient or during the surgical procedure. 14,[16][17][18]20,23,28 It was shown that despite not having achieved correction during the procedure, short-and long--term improvement of pain was observed without any correlation with the radiographic image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation